Low genetic diversity associated with low prevalence of Anaplasma marginale in water buffaloes in Marajo Island, Brazil - Silva, Jenevaldo Barbosa [UNESP]; Fonseca, Adivaldo H.; Barbosa, Jose D.; Cabezas-Cruz, Alejandro; la Fuente, Jose de (Elsevier B.V., 2014)
The rickettsia Anaplasma marginale is the etiologic agent of bovine anaplasmosis, an important tick-borne disease affecting cattle in tropical and subtropical regions of the world. In endemic regions, the genetic diversity of this pathogen is usually related to the high prevalence of the disease in cattle. The major surface protein 1 alpha (MSP1a) has been used as a marker to characterize the genetic diversity and for geographical identification of A. marginale strains. The present study reports the characterization of A. marginale MSP1a diversity in water buffaloes. Blood samples were collected from 200 water buffaloes on Marajo Island, Brazil where the largest buffalo herd is located in the Western hemisphere. Fifteen buffaloes (7.5%) were positive for A. marginale msp1 alpha by PCR. Four different strains of A. marginale with MSP1a tandem repeat structures (4-63-27), (162-63-27), (78-24-24-25-31) and (tau-10-10-15) were found, being (4-63-27) the most common. MSP1a tandem repeats composition in buffalos and phylogenetic analysis using msp1a gene showed that the A. marginale strains identified in buffaloes are closely related to A. marginale strains from cattle. The results demonstrated low genetic diversity of A. marginale associated with low bacterial prevalence in buffaloes and suggested that buffaloes may be reservoirs of this pathogen for cattle living in the same area. The results also suggested that mechanical transmission and not biological transmission by ticks might be playing the major role for pathogen circulation among water buffaloes in Marajo Island, Brazil. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Anaplasma marginale; Buffalo; MSP1a; Genetics; Anaplasmosis